Hubungan Tingkat Stres, Academic Burnout, dan Kecanduan Smartphone dengan Kualitas Tidur pada Mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar - I Wayan Surya Surya Adi Pradhana Bendesa; Irwan Syuhada; Siti Ruqayyah; Bagus Surya Kusumadewa (Universitas Malahayati, 2025)
ABSTRACT Sleep quality is an important aspect of an individual's health. However, decreased sleep quality among young adults, including medical students with high learning intensity has become an increasing global health problem. Factors such as stress levels, academic burnout, and smartphone addiction are known to play a role in sleep loss. High stress levels and burnout symptoms due to academic demands lead to fatigue, while excessive smartphone use can worsen sleep quality. This research aims to analyze the relationship of stress level with sleep quality, academic burnout with sleep quality, and smartphone addiction with sleep quality in students of the Faculty of Medicine, Al-Azhar Islamic University. This research is a quantitative observational analytic with a cross-sectional research design. The sampling technique was carried out by stratified random sampling with a total sample of 83 respondents. Data were analyzed using the Spearman Rank correlation test with a significance value limit of p-value 0.05. The majority of respondents had poor sleep quality (68.7%), mild stress level (45.8%), low academic burnout (66.3%), and smartphoneaddiction (65.1%). Bivariate analysis showed that there was a significant relationship between stress level and sleep quality (p=0.001), academic burnout and sleep quality (p=0.001), and smartphone addiction and sleep quality (p=0.001) in students of the Faculty of Medicine, Al-Azhar Islamic University. There is a significant relationship between stress level, academic burnout, and smartphone addiction with sleep quality in students of the Faculty of Medicine, Al-Azhar Islamic University. Keywords: Sleep Quality, Stress Levels, Academic Burnout, Smartphone Addiction. ABSTRAK Kualitas tidur merupakan aspek penting bagi kesehatan individu. Penurunan kualitas tidur di kalangan dewasa muda, termasuk mahasiswa kedokteran dengan intensitas pembelajaran yang tinggi telah menjadi masalah kesehatan global yang semakin meningkat. Faktor-faktor seperti tingkat stres, academic burnout, dan kecanduan smartphone diketahui berperan dalam penurunan kualitas tidur. Tingkat stres yang tinggi dan gejala burnout akibat tuntutan akademik menyebabkan kelelahan, sementara penggunaan smartphone yang berlebihan dapat memperburuk kualitas tidur. Penelitian ini bertujuan untuk menganalisis hubungan tingkat stres dengan kualitas tidur, academic burnout dengan kualitas tidur, dan kecanduan smartphone dengan kualitas tidur pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar. Penelitian ini merupakan kuantitatif analitik observasional dengan desain penelitian cross-sectional. Teknik pengambilan sampel dilakukan secara stratified random sampling dengan jumlah sampel sebanyak 83 responden. Data dianalisis dengan uji korelasi Rank spearman dengan batas nilai signifikansi p-value 0.05. Mayoritas responden memiliki kualitas tidur buruk (68.7%), tingkat stres ringan (45.8%), academic burnout rendah (66.3%), dan kecanduan smartphone (65.1%). Analisis bivariat menunjukkan terdapat hubungan bermakna antara tingkat stres dengan kualitas tidur (p=0.001), academic burnout dengan kualitas tidur (p=0.001), dan kecanduan smartphone dengan kualitas tidur (p=0.001) pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar. Terdapat hubungan antara tingkat stres, academic burnout, dan kecanduan smartphone dengan kualitas tidur pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar. Kata Kunci: Kualitas Tidur, Tingkat Stres, Academic Burnout, Kecanduan Smartphone